2019
DOI: 10.1007/s40093-019-0265-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural waste on the shrink–swell behavior and cracking dynamics of expansive soils

Abstract: Purpose The swelling characteristics and cracking of expansive clayey soils usually lead to their low yield, and as a result, large areas of expansive soils remain uncultivated and unproductive. There is a need for the development of simple, low-cost technologies which will bring these soils into production. The amendment of expansive clayey soils with agricultural waste products is a key goal for enhancing their production potential. Therefore, a study was conducted to evaluate the ameliorative effects of cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…With intermittent drying and wetting conditions, clay minerals expand and become sticky and muddy by absorbing moisture as they get wet; conversely, the formation of desiccated cracks that appeared on the soil surface shrink during the drying period [155]. Soil cracks are crucial from a different point of view, and they allow increased water infiltration also transport the nutrients to the subsoil [156]. For instance, plant roots may physically be damaged by these cracks.…”
Section: Soil Crack Formationmentioning
confidence: 99%
“…With intermittent drying and wetting conditions, clay minerals expand and become sticky and muddy by absorbing moisture as they get wet; conversely, the formation of desiccated cracks that appeared on the soil surface shrink during the drying period [155]. Soil cracks are crucial from a different point of view, and they allow increased water infiltration also transport the nutrients to the subsoil [156]. For instance, plant roots may physically be damaged by these cracks.…”
Section: Soil Crack Formationmentioning
confidence: 99%
“…Agricultural waste materials have also been used for expansive soil modification, with the advantage of increased environmental protection value. Bagasse fiber, bagasse ash, and rice husk can improve mechanical properties such as shear strength and compressive strength of expansive soils and reduce expansion potential and crack development [156][157][158]. In addition, biochar can inhibit the expansive deformation of such soils [159].…”
Section: Materials Modification Methodsmentioning
confidence: 99%
“…for 10 yr increased liquid limit from 37.5 to 39.1%, plastic limit from 27.2 to 28.5%, and plasticity index from 10.3 to 10.5% (Bhushan & Sharma, 2002). Another study found that mixing rice hulls at 50 g kg −1 with a loam soil and incubating for 280 d increased liquid limit from 37.8 to 39.4%, increased plastic limit from 22.9 to 26.0%, but did not affect plasticity index (Malongweni et al., 2019). In the same study, application of rice hulls at 100 g kg −1 did not affect liquid limit, but it increased plastic limit from 22.9 to 25.1% and decreased plasticity index from 14.9 to 12.7% (Malongweni et al., 2019).…”
Section: Soil Compaction Parametersmentioning
confidence: 99%